Leucoverdazyls as Novel Potent Inhibitors of Enterovirus Replication - Alexandrina S. Volobueva; Tatyana G. Fedorchenko; Galina N. Lipunova; Marina S. Valova; Valeriya A. Sbarzaglia; Anna S. Gladkikh; Olga I. Kanaeva; Natalia A. Tolstykh; Andrey N. Gorshkov; Vladimir V. Zarubaev (Pathogens, 2024)
Enteroviruses (EV) are important pathogens causing human disease with various clinical manifestations. To date, treatment of enteroviral infections is mainly supportive since no vaccination or antiviral drugs are approved for their prevention or treatment. Here, we describe the antiviral properties and mechanisms of action of leucoverdazyls—novel heterocyclic compounds with antioxidant potential. The lead compound, 1a, demonstrated low cytotoxicity along with high antioxidant and virus-inhibiting activity. A viral strain resistant to 1a was selected, and the development of resistance was shown to be accompanied by mutation of virus-specific non-structural protein 2C. This resistant virus had lower fitness when grown in cell culture. Taken together, our results demonstrate high antiviral potential of leucoverdazyls as novel inhibitors of enterovirus replication and support previous evidence of an important role of 2C proteins in EV replication.